Managing Abusive Supervision: How Subordinate Characteristics and Human Resource Management Practices Protect Against Abusive Supervision - Liu, Teng (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2026)
With the rise of research on dark-side leadership, abusive supervision has attracted substantial scholarly attention. However, practical soloutions for mitigating its detrimental effects remain limited, particularly from the perspectives of subordinates and human resource management practices. To address the void, this thesis examines why leaders engage in abusive behaviours, and how their negative consequences may be alleviated once such behaviours occur. Grounded on the Job Demands-Resources (JD-R) framework and Conservation of Resource (COR) theory, the present thesis carries out three empirical studies to address these questions, each informed by different theoretical perspectives. Study 1 combines social influence theory and moral exclusion theory to investigate the effects of subordinate political skill on perceptions of abusive supervision via improving in-role performance (i.e., task performance) and extra-role performance (i.e., organisational citizenship behaviours). Study 2 integrates attribution theory and abusive supervision research to explore the moderating roles of follower perceptions of performance-promotion and injury-initiation attributions in the relationship between abusive supervision and subordinate emotional exhaustion. Study 3 applies the stressor-detachment model to integrate abusive supervision, high performance work systems (HPWS), subordinates' psychological detachment, and strain. Specifically, Study 3 examines both the mediating and moderating roles of psychological detachment in the relationship between abusive supervision and strain. In addition, the role of HPWS is investigated as a contextual factor that moderates the nature of the relationship between abusive supervision and strain via psychological detachment. As the data is not independent (employees nested within supervisors), the proposed hypotheses are tested using multilevel structural equation modeling (MSEM) within Mplus. Study 1 and 2 are carried out based on time lagged data collected from China among 224 individuals nested in 37 teams in a transportation Chinese state-owned enterprise. Study 3 involves a large sample collected from a state-owned energy enterprise in China among 894 individuals nested in 67 teams and 7 company branches (cross-sectional design). Overall, the present study underscores the critical role of subordinate-related factors in both the occurrence and the alleviation of abusive supervision, as well as the role of human resource management (i.e., high-performance work systems) in mitigating its detrimental effects on subordinates. Specifically, the empirical findings suggest that subordinate political skill restricts abusive supervision behaviour via organisational citizenship behaviours (OCB), yet the mediating effect of task performance in the relationship is not significant (Study 1). Contrary to the expectations, subordinate performance-promotion attribution exacerbates, rather than mitigates, the positive influence of abusive supervision on subordinate emotional exhaustion, while the expected exacerbating effect of injury-initiation attribution between abusive supervision and subordinate emotional exhaustion is nonsignificant (Study 2). In addition, high-performance work systems (HPWS) alleviates the negative influence of abusive supervision on subordinates' psychological detachment and in turn their strain (Study 3). While psychological detachment mediates the relationship between abusive supervision and strain, the expected buffering effect of psychological detachment in the relationship is not supported (Study 3). Taken together, the findings make significant contributions to the existing literature by extending the nomological network of abusive supervision regarding how subordinates' characteristics and human resource management practices influence both the occurrence and impacts of abusive supervision. Anchored in the JD-R framework, this thesis integrates complementary theoretical perspectives to unpack the nuanced dynamics surrounding abusive supervision, thereby enriching the existing theoretical foundations of abusive supervision. Finally, the conclusions provide feasible recommendations for coping strategies against abusive supervision in practice and delineate promising avenues for future research.
APPROVED
Keywords: Political skill; Attributions; Emotional exhaustion; High-performance working system (HPWS); Psychological detachment; Abusive supervision; Organizational citizenship behavior; Task performance